2005
DOI: 10.2188/jea.15.180
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Carotenoids Are Inversely Associated with Serum Gamma-glutamyltransferase in Alcohol Drinkers within Normal Liver Function

Abstract: BACKGROUND: Many studies have reported that the consumption of alcohol induces the generation of free radicals. Moreover, recent studies suggest that serum gamma-glutamyltransferase ( γ -GTP) within its normal range might be an early marker of oxidative stress. In this study, we tested the hypothesis that serum antioxidant carotenoids would be inversely associated with serum γ -GTP in alcohol drinkers within normal liver function. METHODS: A total of 266… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…Actually, we observe a negative trend across quartiles of plasma b-carotene for most biological variables clustering in the insulin resistance syndrome, as well as for traditional and new risk factors for type II diabetes and CVD, including CRP and GGT (Best et al, 2005;Wannamethee et al, 2005). This is in agreement with recent investigations describing a negative association between serum b-carotene and GGT in young individuals, adults and alcohol drinkers with normal liver function Lim et al, 2004;Sugiura et al, 2005), and between serum b-carotene and CRP in healthy subjects (Kritchevsky et al, 2000). However, b-carotene intake in the present study shows only a marginally significant relationship with plasma b-carotene, which appears to be intimately associated with many dietary factors.…”
Section: Discussionsupporting
confidence: 92%
“…Actually, we observe a negative trend across quartiles of plasma b-carotene for most biological variables clustering in the insulin resistance syndrome, as well as for traditional and new risk factors for type II diabetes and CVD, including CRP and GGT (Best et al, 2005;Wannamethee et al, 2005). This is in agreement with recent investigations describing a negative association between serum b-carotene and GGT in young individuals, adults and alcohol drinkers with normal liver function Lim et al, 2004;Sugiura et al, 2005), and between serum b-carotene and CRP in healthy subjects (Kritchevsky et al, 2000). However, b-carotene intake in the present study shows only a marginally significant relationship with plasma b-carotene, which appears to be intimately associated with many dietary factors.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, we found that high serum β-cryptoxanthin is associated with a lower risk for liver diseases, such as alcoholic-and non-alcoholic-related liver dysfunction, from a cross-sectional Mikkabi study. 5,6) Carotenoids are mainly accumulated in the liver and combined into lipoprotein for release into the blood circulation. Ingested carotenoids could participate in an antioxidant defense system when present in high concentrations of free radical species in the liver, and these physiological functions of carotenoids could inhibit the development of liver dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…3) Furthermore, we found that individuals with high serum β-cryptoxanthin levels (that is, individuals who regularly ate Satsuma mandarin) had lower risks for liver diseases, 5,6) arteriosclerosis, 7) insulin resistance, 8) metabolic syndrome, 9) low bone mineral density, 10,11) and oxidative stress 4) from a nutritional epidemiologic survey (Mikkabi study) targeting the residents of Mikkabi, a town located in the north ward of Hamamatsu City in Shizuoka Prefecture, which is known as the leading Satsuma mandarin producer in Japan. From these results, we assume that absorbed β-cryptoxanthin is accumulated in several organs and that β-cryptoxanthin may have a protective effect against oxidative stress in several tissues.…”
mentioning
confidence: 89%
“…The concentrations of six serum carotenoids, lutein, lycopene, -carotene, -carotene, -cryptoxanthin, and zeaxanthin, were analyzed by reverse-phase high-performance liquid chromatography (HPLC) using -apo-8 -carotenal as an internal standard at the laboratory of Public Health and Environmental Chemistry, Kyoto Biseibutsu Kenkyusho (Kyoto, Japan), as described previously. 23 Serum total cholesterol and triacylglycerols were measured with an auto-analyzer using commercial kits (Determiner TC-II C for serum total cholesterol, Kyowa-Medics, Inc., Tokyo, Japan; Determiner TG-II C for serum triacylglycerols, Kyowa-Medics, Inc., Tokyo, Japan). Plasma samples were obtained in sampling vials containing sodium fluoride.…”
mentioning
confidence: 99%